Risk Factors and Psychosocial Correlates of Emotionally Negative Dreams in Patients Referred to a Cardiac Rehabilitation Centre - Saeidi, Mozhgan (Malays J Med Sci, 2020)
INTRODUCTION: Dream, as a kind of mental activity, includes various functions such as mood regulation, adjustment and integration of new information with the available memory system. The study was done for assessing the relationship between physiological and psychological components of cardiac diseases with emotionally negative dreams in cardiac rehabilitation. METHODS: At the baseline of this cross-sectional study, 156 patients from Western Iran participated during April–November 2016. People 20 years–80 years able to recall the emotional content of dreams after cardiac surgery entered the study. The Beck depression inventory (BDI), Beck anxiety inventory (BAI), Buss and Perry’s aggression questionnaire (BPAQ) and Schredl’s dream emotions manual were used for collecting data. A binary logistic regression analysis used for the study of the relationship between risk factors and emotionally negative dreams. RESULTS: The mean age of participants was 59 (SD = 9) years (men: 64.1%). The results showed that 25% of patients have negative emotional content. After adjustment for demographic variables, the results showed that increased anxiety [adjusted odds ratio (adj OR) = 1.08 [1.01–1.16], P = 0.020] and anger (adj OR = 1.03 [1.00–1.06], P = 0.024) and hypertension (adj OR = 2.71 [1.10–6.68], P = 0.030) can predict the dreams with negative content significantly. CONCLUSION: The increasing rates of anxiety and anger and history of hypertension are related to increasing dreams with the negative emotional load. The control of risk factors of dreams with negative emotional load can be the target of future interventions.